Evaluation of Protective Effects of Pomegranate Seed Oil on Experimental Osteoporosis in Rats - Farzaneh Khodadadi; Zahra Moosavi; Soheil Sadr; Ali Mirshahi; Hossein Kazemi Mehrjerdi (Iranian Journal of Veterinary Surgery, 2024)
Osteoporosis is characterized by a reduction of bone mass and destruction of bone structures, followed by high bone fragility and susceptibility. This study aims to evaluate the protective effects of pomegranate seed oil (PSO) on experimental osteoporosis in rats. Twenty-four female Wistar rats were divided into four groups: sham-operated (Sham = 6), Sham with PSO treatment (Sham+PSO = 6), ovariectomized (OVX = 6), and ovariectomized with PSO treatment (OVX+PSO = 6). OVX+PSO and Sham+PSO groups received 0.1 ml of pomegranate juice daily, and OVX and Sham groups received the same amount of paraffin oil. After eight weeks, the femur and tibia bones were removed, and the structure and metabolism of samples were assessed by histological examination. The average thickness of femoral neck trabeculae in group OVX was significantly lower than in groups Sham+PSO and Sham (p < 0.05). Regarding the number of trabeculae in the neck of the femur, a significant difference was observed between groups OVX and Sham+PSO (p < 0.05). Furthermore, trabecular separation in group OVX was significantly more than in the other three groups (p < 0.05). The trabecular separation in group OVX+PSO compared to groups Sham+PSO and Sham was significantly higher (p < 0.05). A histopathologic examination of the upper metaphysis of the tibia indicated that the number of bone trabeculae in Sham+PSO was only statistically significant in the OVX group (p = 0.018). It was also found that the average thickness of bone trabeculae in the OVX+PSO and Sham groups was significantly lower than in the Sham+SO group. The results of the present study suggest that pomegranate seed oil, having estrogenic compounds, can prevent osteoporosis in rats caused by ovariectomy.